EMG-Based Model Predictive Control for Physical Human–Robot Interaction: Application for Assist-As-Needed Control - Teramae, Tatsuya; Noda, Tomoyuki; Morimoto, Jun (IEEE robotics and automation letters, 2018)
In this letter, we propose an electromyography (EMG)-based optimal control framework to design physical human-robot interaction for rehabilitation and develop a novel assist-as-needed (AAN) controller based on a model predictive control (MPC) approach. To enhance the recovery of motor functions, encouraging the voluntary movements of patients is necessary while a therapist is assisting them. Therefore, in an AAN control framework, the robot only assists the deficient torque to generate a target movement. In our study, we first estimate the joint torque of a patient from measured EMG signals and then derive the deficient joint torque to generate the target movements by considering the patient's estimated joint torque with an MPC method. Results showed that our proposed method adaptively derived the necessary torque to follow the target elbow joint trajectories based on the subject's voluntary movements.